Development of 8-inch Key Processes for Insulated-Gate Bipolar Transistor. (September 2015) - Liu, Guoyou; Ding, Rongjun; Luo, Haihui
ABSTRACT: Based on the construction of the 8-inch fabrication line, advanced process technology of 8-inch wafer, as well as the fourth-generation high-voltage double-diffused metal-oxide semiconductor (DMOS+) insulated-gate bipolar transistor (IGBT) technology and the fifth-generation trench gate IGBT technology, have been developed, realizing a great-leap forward technological development for the manufacturing of high-voltage IGBT from 6-inch to 8-inch. The 1600 A/1.7 kV and 1500 A/3.3 kV IGBT modules have been successfully fabricated, qualified, and applied in rail transportation traction system.